ENVIRONMENTAL TERRORISM IN PETER WUTEH VAKUNTA’S GREEN RAPE - Gamal Elgezeery (European Scientific Journal, ESJ, 2014)
This article deals with the issue of environmental terrorism in Peter Wuteh Vakunta’s Green Rape: Poetry for the Environment. Vakunta uses his poetic practice to engage with the interdisciplinary issues related to the intersection of poetry, culture, environmental studies and poetics, and environmental activism. The article begins with tracing the ramifications of the terminology of terrorism related to the environment. Then it shows how Vakunta views environmental terrorism from a somewhat different perspective. He devotes many poems in this collection to this issue and shows how it is not limited to the acts of direct violence but pervades numerous activities when we get in contact with the environment or go on with our daily routines. This terrorism ranges from war and oil spills to littering and over-consumption.